SOME COMMENTS ON THE URBAN PLANNING CULTURE OF THE GREAT KHOREZMSHAHS PERIOD (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the article, the issues of interrelation between the culture of urban planning and ancient settlements in the second half of the 12th century and the beginning of the 13 th century were considered.